Epidemiology of non-tuberculous mycobacterial diseases in Slovakia during the years 2016–2021 - Dohál, Matúš; Porvazník, Igor; Krivošová, Michaela; Solovič, Ivan; Mokrý, Juraj (Respiratory physiology & neurobiology, 2023)
Nontuberculous mycobacteria (NTM) are opportunistic human pathogens found worldwide, primarily in the environment. They predominantly affect the lungs, especially in individuals with compromised immune systems. Recent studies suggest an increasing incidence of NTM disease; however, their actual clinical impact in Slovakia remains uncertain. In this study, we conducted a retrospective analysis using a representative collection of NTM cases in the country. We searched the national database for patients with positive NTM cultures between January 2016 and December 2021. A total of 1355 NTM-positive cultures were identified in Slovakia, with no significant increase observed during the study period. Among these, 358 cases (26.4%) were confirmed as NTM disease. The incidence of the disease was notably higher in individuals over 55 years old (p < 0.0001). Moreover, women diagnosed with NTM disease exhibited a significantly higher average age than men (p = 0.0005). The majority of NTM disease cases were attributed to Mycobacterium (M.) intracellulare (39.9%) and M. avium (38.5%). Geographically, the highest incidence of NTM disease was observed in the Bratislava region (10.69 per 100,000 population). •Compared to other European countries, Slovakia is among the countries with the highest prevalence of NTM disease.•Since 2010, there has been a significant upward trend in the incidence of NTM diseases.•Results indicating significant changes in the circulation of individual NTM strains in recent years.•The incidence rate for NTM disease was significantly higher in age groups 55–64 and > 65.